2007
DOI: 10.1017/s0959269507002827
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the schwa/zero alternation in French clitics: experimental and non-experimental evidence

Abstract: This article examines the phonological status of schwa in clitics, in particular whether or not schwa should be included in their lexical representation. Several distributional and experimental arguments pointing to the lexical status of clitic schwas are reviewed and are shown to be inconclusive, due to the existence of additional data that suggest a different interpretation not involving underlying schwas. The discussion includes experimental results that fail to show residual lip rounding in the vicinity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Dell (1985), for example, treats some word boundary schwas as underlying, such as the one in (5d), consistent with the orthography. Schwas at clitic boundaries are especially controversial, and authors are divided as to whether to treat them as epenthetic (Côté 2000;Côté & Morrison 2007;Kaplan 2016) or underlying (Tranel 1981;Lyche & Durand 1996;Jetchev 1999). We'll focus on the distinction between schwas at word boundaries and clitic boundaries, since those are the two contexts we consider in our experiment and model.…”
Section: (5)mentioning
confidence: 99%
“…Dell (1985), for example, treats some word boundary schwas as underlying, such as the one in (5d), consistent with the orthography. Schwas at clitic boundaries are especially controversial, and authors are divided as to whether to treat them as epenthetic (Côté 2000;Côté & Morrison 2007;Kaplan 2016) or underlying (Tranel 1981;Lyche & Durand 1996;Jetchev 1999). We'll focus on the distinction between schwas at word boundaries and clitic boundaries, since those are the two contexts we consider in our experiment and model.…”
Section: (5)mentioning
confidence: 99%
“…The only French determiner for which a gender congruency effect was tested so far is the definite singular determiner. As mentioned above, the two genders share the same pronunciation before vowels, and the alternation between the "full" and "reduced" pronunciations can easily be accounted for by a general phonological process (see Côté & Morrison, 2007 for a summary of the phonological literature on le and other clitics). Other determiners in French differ from the singular definite determiners in one or several dimensions.…”
Section: The Current Studymentioning
confidence: 99%
“…They further reported a gap between the first and second modes and concluded that schwa deletion in this language is a categorical process. Several studies, however, also reported evidence that French nonschwa variants retain acoustic and/ or articulatory traces of the schwa vowel (Barnes & Kavitskaya, 2002;Rialland, 1986; but see Côté & Morrison, 2007). Bürki, Ernestus, Gendrot, Fougeron, and Frauenfelder (2011a) suggested that occurrences of nonschwa variants may result from two distinct processes, a specific categorical deletion process and a general gradient reduction process.…”
Section: Acoustic Deletions/reductionsmentioning
confidence: 99%